Chứng minh các phương trình sau luôn có nghiệm a) x(x−a)+x(x−b)+(x−a)(x−b)=0 b) (x−a)(x−b)+(x−b)(x−c)+(x−c)(x−a)=0 c) x2+(a+b)x−2(a2−ab+b2)=0 d) 3x2−2(a+b+c)x+ab+bc+ca=0Giải: a) x(x−a)+x(x−b)+(x−a)(x−b)=0 $\Leftrightarrow 3x^2-2(a+b)x+ab=0$$\Delta '=(a+b)^2-3ab=a^2-ab+b^2=\frac{(a-b)^2}2+\frac{a^2+b^2}2\geq 0$suy ra PT luôn có nghiệm b) (x−a)(x−b)+(x−b)(x−c)+(x−c)(x−a)=0⇔3x2−2(a+b+c)x+ab+bc+ca=0 Δ′=(a+b+c)2−3(ab+bc+ca)=a2+b2+c2−ab−bc−ca =(a−b)2+(b−c)2+(c−a)22≥0Suy ra PT (b) luôn có nghiệm. c) x2+(a+b)x−2(a2−ab+b2)=0 Δ′=(a+b)2+4.2(a2−ab+b2)=9a2−6ab+9b2=8a2+(a−3b)2≥0Suy ra PT (c) luôn có nghiệm. Câu (d) tương tự câu (b)
Chứng minh các phương trình sau luôn có nghiệm a) x(x−a)+x(x−b)+(x−a)(x−b)=0 b) (x−a)(x−b)+(x−b)(x−c)+(x−c)(x−a)=0 c) x2+(a+b)x−2(a2−ab+b2)=0 d) 3x2−2(a+b+c)x+ab+bc+ca=0Giải: a) x(x−a)+x(x−b)+(x−a)(x−b)=0 $\Leftrightarrow (x+1)(x-a)(x-b)=0$$\Leftrightarrow \left[\ \begin{array}{l} x=-1\\x=a\\ x=b \end{array} \right.$ b) (x−a)(x−b)+(x−b)(x−c)+(x−c)(x−a)=0⇔3x2−2(a+b+c)x+ab+bc+ca=0 Δ′=(a+b+c)2−3(ab+bc+ca)=a2+b2+c2−ab−bc−ca =(a−b)2+(b−c)2+(c−a)22≥0Suy ra PT (b) luôn có nghiệm. c) x2+(a+b)x−2(a2−ab+b2)=0 Δ′=(a+b)2+4.2(a2−ab+b2)=9a2−6ab+9b2=8a2+(a−3b)2≥0Suy ra PT (c) luôn có nghiệm. Câu (d) tương tự câu (b)
Chứng minh các phương trình sau luôn có nghiệm a)
x(x−a)+x(x−b)+(x−a)(x−b)=0 b)
(x−a)(x−b)+(x−b)(x−c)+(x−c)(x−a)=0 c)
x2+(a+b)x−2(a2−ab+b2)=0 d)
3x2−2(a+b+c)x+ab+bc+ca=0Giải: a)
x(x−a)+x(x−b)+(x−a)(x−b)=0 $\Leftrightarrow
3x
^2-2(a+
b)x
+ab=0$$\
De
lta
'=(a+b)^2-3ab=a^2-ab+b^2=\f
rac{
(a
-b)^2}2+\fra
c{
a^2+b^2}
2\geq 0$suy ra
PT luôn
có ngh
iệm b)
(x−a)(x−b)+(x−b)(x−c)+(x−c)(x−a)=0⇔3x2−2(a+b+c)x+ab+bc+ca=0 Δ′=(a+b+c)2−3(ab+bc+ca)=a2+b2+c2−ab−bc−ca =(a−b)2+(b−c)2+(c−a)22≥0Suy ra PT (b) luôn có nghiệm. c)
x2+(a+b)x−2(a2−ab+b2)=0 Δ′=(a+b)2+4.2(a2−ab+b2)=9a2−6ab+9b2=8a2+(a−3b)2≥0Suy ra PT (c) luôn có nghiệm. Câu (d) tương tự câu (b)